Stakeholder Preference Assessment in Implementation Research: Application of Best-worst Scaling - MAO Run; CAI Yiyuan; YANG Wei; LIU Zhiguo; LINGHU Lang; CHEN Jiajia; LIANG Mengjiao; HUANG Lieyu; LIU Siyuan; XU Dong (Xiehe Yixue Zazhi)
In the field of healthcare service, it is crucial to optimize medical innovation services by combining the preferences of health service providers and demanders (i.e., stakeholders). The best-worst scaling (BWS) method is a recently developed stated preference method for assessing preferences with distinctive advantages. Nevertheless, there is a lack of a comprehensive introduction to stakeholder preference assessment using BWS, thus constraining its applications and promotion. This paper introduces the process of using BWS to assess service providers' preferences for the Shared Medical Appointment for diabetes (SMART), an integrated healthcare service of medicine and health management, in the hope of providing reference for researchers for promoting the use of BWS in implementation research.